Heritage Site Management in Focus of Interpretation and Presentation of Battle Zones: Case of Gallipoli Historical Site - Bektaş, Bilge N.; Nizamoğlu, Serdar M.A. (ICONARCH International Congress of Architecture and Planning, 2017)
History of humanity has been evolved through natural disasters, scarcities, outbreaks, inventions, discoveries, wars, revolutions, devolutions, victories, losses, exile, displacements, migrations, massacres and along with others that is directly or indirectly shaped by human actions. Some events occurred through the evolution of humanity resulted in breaking points. These breaking points have shaped collective memory. With this respect, Gallipoli Peninsula, the place of Gallipoli Campaign in the First World War, is the scene of a breaking point and a case of battlefield that has placed in collective memory. Many visitors, mainly from Turkey, Australia and New Zealand, visit the peninsula annually to commemorate Gallipoli Campaign and those people who lost their lives during the war. For that sense, conserving the collective memory and shedding light on signs linked to the memory are vital for transferring historical reality to the next generations and enduring collective memory. This paper aims to constitute a heritage site management model for Gallipoli Peninsula by focusing on interpretation and presentation of battle zones through revealing the signs and remains of war.